Poster: A Mobile Application for Voice and Remote Control of Programmable Instruments - YAYLA, AYŞE; KORKMAZ, HAYRİYE (SPRINGER INTERNATIONAL PUBLISHING AG, 2019)
The purpose of this work is to add a new feature to bench-type conventional instruments used in Electrical and Electronics Engineering Laboratory which do not have any voice recognition and wireless communication technology. By this way, the user can control these instruments/devices remotely with voice commands and also monitor the results/values in graphical or numerical/text format as well over a mobile device screen. The only limitation is that such instruments should have a driver supported by any software such as NI LabVIEW and a PC connectivity interface such as USB, GPIB or LXI (LAN extensions for Instrumentation). Controlling the instruments (such as oscilloscope or signal generators which are frequently used for training purposes and whose functions are manually set) over a mobile device with voice commands will make life easier for disabled students who especially have difficulties in using their hands.
Keywords: LabVIEW; Android; Google Speech Recognition; Remote control; Internet of Things